THE CULTURAL VALUES ​​OF THE ISLAND’S INDIGENOUS PEOPLE - Titaley, Elsina; Watloly, Aholiab (Sosiohumaniora, 2021)
The cultural values of the indigenous peoples in the form of local wisdom are identities and guidelines that must be upheld. Currently, the cultural values of the indigenous peoples in the islands are already at a weakening of their identity. So that the purpose of this research is to provide a comprehensive understanding to the indigenous people of the island of Asilulu to maintain the beauty values that have been preserved since the time of their ancestors several hundred years ago. The method used in this research is qualitative in the form of case studies to re-explore the cultural values of society. It should be noted that the people in this country are experiencing a weakening of cultural values which is marked by the loss of some traditional institutions that were previously preserved and upheld. This attenuation occurs as a result of the influence of external factors and internal factors in society. The results of the research prove that the community has the desire to revive these cultural values.